Pengaruh Nilai Transaksi Pembayaran Non Tunai Terhadap Pertumbuhan Ekonomi Indonesia Sebagai Isu Prioritas Indonesia Dalam G20 - As Sayyidah Az Zuhriyyah; Nurbetty Herlina Sitorus (Departement of Mathematics Education, 2023)
The aim of this research is to see the influence of the value of non-cash payment transactions on the production index, a proxy for Indonesia's economic growth in the short and long term. The analytical method used is the Error Correction Model (ECM) with research data of 90 observations, research period January 2015 to June 2022. The research variables are production index, proprietary channel transaction value, APMK transaction value, RTGS transaction value, and SKNBI transaction value . The results of this research show that the value of proprietary channel transactions has a positive and significant effect in the short and long term. The APMK transaction value has an insignificant positive effect in the short term and a significant positive effect in the long term. The RTGS transaction value has an insignificant positive effect in the short term, and an insignificant negative effect in the long term. And the SKNBI transaction value has a significant positive effect in the short and long term on the production index.